Yersinia enterocolitica detection in pork products: Evaluation of isolation protocols. (December 2020) - Peruzy, M.F.; Aponte, M.; Proroga, Y.T.R.; Capuano, F.; Cristiano, D.; Delibato, E.; Houf, K.; Murru, N.
Abstract: Conventional methods for Yersinia enterocolitica detection in food samples are generally considered inadequate. Problems arise from the presence of the so-called "background flora", coupled to the low contamination level of the pathogen. Since, data on the microbial ecology occurring in competitive microflora are still lacking, MALDI TOF MS was used for strains 'identification after enrichment in PSB or ITC broths, and after plating on selective CIN medium at different incubation times. SYBR Green Real time PCR was used for the Y. enterocolitica strains' detection (4/O:3, 1A/O:5) in experimentally contaminated foods, as well as in naturally contaminated samples. A higher number of different bacterial genera (10 on CIN and 18 on PCA) was recorded after enrichment in PSB, whilst enrichment in ITC led to recovery of 6 and 10 genera on CIN and PCA, respectively. Yersiniaceae was the dominant family on the first day of incubation, but on the second day the percentage of isolation considerably decreased. By testing experimentally contaminated samples, substantial difficulties were encountered. The biotype 1A was always detected, whereas strain 4/O:3 proved to be poorly competitive. Based on the data, the enrichment media PSB and ITC, currently proposed for Y. enterocolitica detection, need to be improved to promote a successful pathogen's recovery. Highlights: Evaluation of hurdles associated with Yersinia enterocolitica detection in pork products. Y. enterocolitica detection proved to be affected by the length of the enrichment. The "accompanying flora" of Y. enterocolitica was evaluated by MALDI TOF MS. Colonies were isolated after enrichment in PSB & ITC broths followed by CIN & PCA. Genera occurring in isolation media are affected by time & temperature of incubation.